The Efficacy and Safety of Low Molecular Weight Heparin Administration to Improve Survival of Cancer Patients: A Systematic Review and Meta-Analysis - Montroy, Joshua; Lalu, Manoj M.; Auer, Rebecca C.; Grigor, Emma; Mazzarello, Sasha; Carrier, Marc; Kimmelman, Jonathan; Fergusson, Dean A. (Thrombosis and Haemostasis, 2020)
Background Low molecular weight heparins (LMWH) are often used as a first-line therapy for the prevention of thrombosis in cancer patients. Preclinical evidence from animal models suggests that LMWH may have antimetastatic properties. Clinical evidence of this effect is inconclusive. The objective of this systematic review is to evaluate the effect of LMWH on overall survival in patients with solid tumor malignancies.Methods MEDLINE, Embase, and The Cochrane Central Register of Controlled trials were searched from inception to November 26, 2018. We included randomized controlled trials that compared LMWH to placebo, a no-treatment arm, or a short-term prophylactic course of LMWH in adult patients with solid tumors. The primary outcome was overall survival. Secondary outcomes included progression-free survival, the occurrence of venous thromboembolism, and major bleeding events. The risk of bias was assessed in duplicate using the Cochrane Risk-of-Bias tool.Results Forty-five articles were included in the review. Overall, no difference in overall survival was observed between groups (risk ratio: 1.00; 95% confidence interval: 0.98–1.02; I2 = 36.5%). In our a priori defined subgroup analyses, the effect was not shown to vary by the type of LMWH, duration of LMWH use, length of study follow-up, comparator used in the study, or the setting in which the LMWH was administered. The majority of studies had an unclear risk of bias for at least one methodological criterion.Conclusion Although LMWH is thought to possess antimetastatic properties and thus have the potential to improve survival in cancer patients, existing data do not support this hypothesis.
Keywords: low molecular weight heparin; cancer; survival; systematic review